2019
DOI: 10.1186/s12872-019-1122-3
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of long non-coding RNA nuclear enriched abundant transcript 1 promotes cell proliferation and inhibits cell apoptosis by targeting miR-193a in myocardial ischemia/reperfusion injury

Abstract: Background: This study aimed to investigate the effect of long non-coding RNA nuclear enriched abundant transcript 1 (lnc-NEAT1) on cell proliferation and apoptosis in myocardial ischemia/reperfusion (I/R) injury cells, and explore its target miRNAs. Methods: H9c2 cells were cultured in oxygen and glucose deprivation followed by reperfusion (OGD/R) condition to construct a myocardial I/R injury model. Blank shRNA and lnc-NEAT1 shRNA were transferred into normal H9c2 cells and I/R injury H9c2 cells as Normal&sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…31 Overexpression of the lncRNA NEAT1 was also observed in myocardial I/R injury cells compared with normal myocardial cells. 32 The lncRNA MALAT1 showed more than fourfold higher expression in patients with T2DM compared with healthy controls. Among patients with T2DM, higher expression of the lncRNA MALAT1 was linked with weight loss, blurred vision, smoking, and alcoholism compared with the corresponding counterparts without these parameters.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…31 Overexpression of the lncRNA NEAT1 was also observed in myocardial I/R injury cells compared with normal myocardial cells. 32 The lncRNA MALAT1 showed more than fourfold higher expression in patients with T2DM compared with healthy controls. Among patients with T2DM, higher expression of the lncRNA MALAT1 was linked with weight loss, blurred vision, smoking, and alcoholism compared with the corresponding counterparts without these parameters.…”
Section: Discussionmentioning
confidence: 95%
“…31 Overexpression of the lncRNA NEAT1 was also observed in myocardial I/R injury cells compared with normal myocardial cells. 32 …”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that lncRNAs serve a significant role in the regulation of the myocardial IR process ( 68 ). For example, Ren et al ( 69 ) investigated the effect of lncRNA nuclear enriched abundant transcript 1 (lnc-NEAT1) on cell proliferation and apoptosis in MIRI and observed that lnc-NEAT1 is overexpressed in MIRI compared with levels in normal cardiomyocytes. Downregulation of lnc-NEAT1 enhances cell proliferation and inhibits cell apoptosis by targeting miR-193a in IR injury H9C2 cells ( 69 ).…”
Section: Roles Of Hif-1α In Mirimentioning
confidence: 99%
“…For example, Ren et al ( 69 ) investigated the effect of lncRNA nuclear enriched abundant transcript 1 (lnc-NEAT1) on cell proliferation and apoptosis in MIRI and observed that lnc-NEAT1 is overexpressed in MIRI compared with levels in normal cardiomyocytes. Downregulation of lnc-NEAT1 enhances cell proliferation and inhibits cell apoptosis by targeting miR-193a in IR injury H9C2 cells ( 69 ). Li et al ( 70 ) assessed the role of lncRNA H19 in the regulation of MIRI and suggested that H19 expression levels are downregulated in IR hearts of mice and cardiomyocytes treated with H 2 O 2 .…”
Section: Roles Of Hif-1α In Mirimentioning
confidence: 99%
“…Previous studies have reported that non-coding RNAs serve an important role in regulating pathophysiological processes of myocardial I/R injury, including cell differentiation, proliferation, apoptosis, necrosis and autophagy ( 4 7 ). Non-coding RNAs are functional RNAs that are transcribed from non-coding DNAs and have important regulatory functions, although they lack the potential of protein coding ( 8 ).…”
Section: Introductionmentioning
confidence: 99%